2015
DOI: 10.1111/pbi.12476
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β‐glucosidase increases trichome density and artemisinin content in transgenic Artemisia annua plants

Abstract: Artemisinin is highly effective against multidrug-resistant strains of Plasmodium falciparum, the etiological agent of the most severe form of malaria. However, a low level of accumulation of artemisinin in Artemisia annua is a major limitation for its production and delivery to malaria endemic areas of the world. While several strategies to enhance artemisinin have been extensively explored, enhancing storage capacity in trichome has not yet been considered. Therefore, trichome density was increased with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 63 publications
(87 reference statements)
0
40
0
Order By: Relevance
“…S1). Sample treatment followed the method previously reported by Singh et al (2015). Pictures were imaged via extreme-resolution analytical field emission SEM (Jeol, Japan, and Thermo, USA).…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…S1). Sample treatment followed the method previously reported by Singh et al (2015). Pictures were imaged via extreme-resolution analytical field emission SEM (Jeol, Japan, and Thermo, USA).…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Trichomes have been regarded as a perfect system in which to study cell development and secondary metabolite synthesis in the model plants Arabidopsis [10][11][12][13][14][15][16], tomato [17][18][19][20][21][22][23], and Artemisia annua [24][25][26][27][28][29][30], and many genes that are involved in trichome differentiation have been identified, especially various transcription factors (TFs) encoding genes, such as positive regulators of GLABROUS 3 (GL1, GL2, and GL3) and ENHANCER OF GLABROUS 3 (EGL3), TRANSPARENT TESTA 1 (TTG1 and TTG2) and repressors of TRIPTYCHON (TRY), CAPRICE (CPC), ENHANCER OF TRY, CPC 1 (ETC1, ETC2, and ETC3), and TRICHOMELESS 1 (TCL1 and TCL2) [6,12,13,16]. Moreover, an increasing number of studies have indicated that trichomes seem to be an excellent model in which to study the molecular mechanisms of secondary cell wall deposition and fiber synthesis [31,32], which have been well studied in plants.…”
Section: Introductionmentioning
confidence: 99%
“…One strategy to increase squalene could be to increase sink capacity by sequestering squalene in storage compartments such as lipid droplets (Wang et al, 2015) or additional trichomes (Lange, 2015). Trichome density could be increased via transgenic expression of b-glucosidase (Jin et al, 2011), which improves artemisinin yields in transgenic Artemisia annua (Singh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%